2009
DOI: 10.1007/s10600-009-9328-8
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoids from Cephalaria grossheimii

Abstract: We have continued research on chemical components from representatives of the family Dipsacaceae Lindl. (teasel) [1, 2], one species of which, Cephalaria grossheimii Bobr., is endemic to Azerbaidzhan [3]. According to Cherepanov [4], this species is synonymous with C. kotschyi Boiss et Hoh. However, this contradicts the literature on the phytochemistry of these plants. Thus, roots of C. kotschyi contained the alkaloids gentianine, gentianadine, and gentianaine [5] whereas alkaloids were not observed in those o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…This compound was confirmed in Cephalaria grossheumii Bobr. species [26]. Compounds 21, 24 and 28 were identified as apigenin derivatives.…”
Section: Qualitative Lc-dad-ms 3 Analysis Of the Chemical Compositionmentioning
confidence: 97%
See 1 more Smart Citation
“…This compound was confirmed in Cephalaria grossheumii Bobr. species [26]. Compounds 21, 24 and 28 were identified as apigenin derivatives.…”
Section: Qualitative Lc-dad-ms 3 Analysis Of the Chemical Compositionmentioning
confidence: 97%
“…335 for apigenin derivatives (21, 24, 28), and ca. 350 for luteolin and quercetin glycosides (22,23,26). Compound 26 showed deprotonated ion at m/z = 463.…”
Section: Qualitative Lc-dad-ms 3 Analysis Of the Chemical Compositionmentioning
confidence: 99%
“…IR spectra were obtained on an ATI Mattson Genesis Series Fourier transform infrared spectrophotometer. NMR experiments were performed on Varian AS 400 MHz and Varian ASP 600 MHz instruments in DMSO-d 6 . All chemical shifts were given in ppm units with reference to tetramethylsilane (TMS) as an internal standard and the coupling constant (J) were in Hz.…”
Section: Generalmentioning
confidence: 99%
“…This wide range of usages has led to investigations on different Cephalaria species. Many chemical identification studies have been reported that this genus contains triterpenoid saponins, flavonoids, alkaloids, furofuranic lignans and iridoids [5][6][7][8][9][10][11][12][13]. According to these literatures, it is also known that these compounds have different activities including antimicrobial, hemolytic, hypolipidemic, immunomodulating and cytotoxic [7-8, 11-12, 14].…”
Section: Introductionmentioning
confidence: 99%
“…In light of all of this knowledge, we decided to investigate the glycosidic compounds in Cephalaria elmaliensis (Dipsacaceae). Previous phytochemical investigations on different Cephalaria species have reported a number of triterpene saponins, iridoids, flavonoids, alkaloids, lignans, and their glycosidic compounds [4][5][6][7][8][9][10][11][12][13][14][15]. Triterpene saponins are the major examples of these types of substances [4][5][6][7][8][9][10][11].…”
mentioning
confidence: 99%